Stepwise topochemical fluorination of SrCrO3 perovskite via a super-structured oxide. Issue 50 (5th June 2019) - Su, Yu; Tsujimoto, Yoshihiro; Fujii, Kotaro; Masubuchi, Yuji; Ohata, Hirohito; Iwai, Hideo; Yashima, Masatomo; Yamaura, Kazunari
Abstract : Topochemical reactions between SrCrO3 and g-C3 N4 /PVDF yielding SrCrO2.8 /SrCrO2.8 F0.2 are presented. Abstract : A topochemical reaction between SrCrO3 and polyvinylydene fluoride yields the new fluorinated phase SrCrO2.8 F0.2 . The transformation proceeds via a reduced oxide intermediate (SrCrO2.8 ) that can be isolated as a single phase by the reaction between SrCrO3 and g-C3 N4 . The fluoride ions randomly occupy anion sites despite an oxygen-vacancy ordered structure in SrCrO2.8 .